Characterization of smart PZT transducer and admittance signatures using PZT-structure interaction models for structural health monitoring - Annamdas Venu Gopal Madhav (2008)
The monitoring of existing aero, civil and mechanical (ACM) structures has become a regular feature after the world witnessed the various recent deadly failures and damages, due to natural calamities or continuous usage of structures causing wear and tear. The last few years have witnessed rapid development in the areas of nondestructive evaluation (NDE) based Structural health monitoring (SHM) by the emergence of the electromechanical impedance (EMI) technique. This technique employs piezoelectric-ceramic (PZT) transducers for the prediction of structural response known as electromechanical (EM) admittance. Engineering structures can be classified into two categories based on their stiffness, those which are more stiffer and those which are less stiff than the PZT material. Surface bonded and Embedded PZT transducers are more efficient when they are more stiffer and less stiff than the host structure respectively. Both types of PZT transducers are important in the EMI based NDE of the two categories of engineering structures. However, surface bonded PZT transducers have seen more prominent applications in the recent past in SHM. This research developed both surface bonded and embedded PZT- structure interaction models for SHM of existing and future ACM structures.